1980
DOI: 10.1042/bj1860483
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of alcohol dehydrogenase and ethanol metabolism by sex hormones in the spontaneously hypertensive rat. Effect of chronic ethanol administration

Abstract: In young (4-week-old) male and female spontaneously hypertensive (SH) rats, ethanol metabolic rate in vivo and hepatic alcohol dehydrogenase activity in vitro are high and not different in the two sexes. In males, ethanol metabolic rate falls markedly between 4 and 10 weeks of age, which coincides with the time of development of sexual maturity in the rat. Alcohol dehydrogenase activity is also markedly diminished in the male SH rat and correlates well with the changes in ethanol metabolism. There is virtually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(43 citation statements)
references
References 24 publications
5
38
0
Order By: Relevance
“…The emergence of gender differences in ADH activity coincides with sexual development: a relative increase in ADH activity in females is not detected until the sixth week of age, the age at which rodents reach sexual maturity, and remains elevated thereafter (Rao et al, 1997). Second, estrogen increases hepatic ADH activity, whereas testosterone decreases it (Rachamin et al, 1980;Harada et al, 1998). Similar to ADH, estrogen also Fig.…”
Section: Discussionmentioning
confidence: 89%
“…The emergence of gender differences in ADH activity coincides with sexual development: a relative increase in ADH activity in females is not detected until the sixth week of age, the age at which rodents reach sexual maturity, and remains elevated thereafter (Rao et al, 1997). Second, estrogen increases hepatic ADH activity, whereas testosterone decreases it (Rachamin et al, 1980;Harada et al, 1998). Similar to ADH, estrogen also Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Studies in rodents have shown that ethanol can increase ADH activity in male rats by reducing testosterone levels (Rachamin et al 1980). The doses of ethanol delivered to rats or mice via the use of liquid diets does not have significant effects on liver ADH.…”
Section: Alcohol Dehydrogenasesmentioning
confidence: 99%
“…Many previous studies (8,12,13,16,(20)(21)(22) showed increases in liver ADH activity during uremia produced by partial nephrectomy after stress induced by immobilization and after hypophysectomy. Further, uremia and various forms of stress in man all result in a fall in plasma testosterone levels.…”
Section: Effect Of Testosterone On Liver Adh Activities In Orchiectommentioning
confidence: 99%